Analisis Kualitas Website Terhadap Kepuasan Pengguna Menggunakan Metode WebQual 4.0 dan End User Computing Satisfaction (EUCS): (Studi Kasus : Website Kantor Sekretariat Daerah Kab.Ogan Ilir) - Ayu Sari, Amelisa Fitri; Damayanti, Nita Rosa; Fatmasari, Fatmasari; Farozi, M. (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2023)
Abstract : As communication and information technology develops rapidly, the Regional Secretary of the Ogan Ilir government has a website for informing the public about news or announcements of activities they are carrying out. However, another problem that is often encountered nowadays is that the information obtained is still not updated enough and many people still don't know about the Ogan Ilir government regional secretary's website. Therefore, there is a need for research to measure satisfaction with the Ogan Ilir government's Regional Secretary website which aims to determine the status of user satisfaction and the factors that influence satisfaction so whether this website is suitable to be used as a reference in obtaining information. The model used in this research is the WebQual 4.0 model which consists of 3 variables, namely Usability, Information Quality, Service Interction Quality, and the End User Computing Satisfaction model consisting of 1 variable, namely Timeliness. This research uses a quantitative approach, sampling is carried out using purposive sampling and accidental sampling techniques, data processing and analysis uses SmartPLS 3.0.